Stature estimation from the hand dimensions in the Eastern Saudi Arabian adult male population - Madadin, Mohammed; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Anthropometry is widely used in preliminary forensic investigations involving the identification of unknown dismembered body parts. Stature estimation is an important indicator of forensic identification considered during such initial investigations. Different populations have different body sizes and proportions that affect the forensic anthropometric estimation of stature. Hence, the need for population-specific databases and analyses. The present study was conducted with the objective of estimating stature from the hand dimensions in the Eastern Saudi Arabian adult male population.Methods: The present study included 200 Eastern Saudi Arabian males aged from 20 to 56 years. Stature and hand dimensions of hand length, palm length, and hand breadth were measured as per standard anthropometric procedures. Linear and multiple regression equations were derived to estimate stature from the aforementioned hand dimensions.Results: Correlation coefficients between stature and the aforementioned hand dimensions were found to be statistically significant. The hand length and palm length showed higher correlation coefficients than the hand breadth. Single variable linear regression and multi-variable linear regression equations were derived to estimate stature from the hand dimensions. Higher correlation coefficients were obtained for multi-variable linear regression than single variable linear regressions.Conclusions: In conclusion, hand dimensions can be used as a reliable predictor to estimate stature in the Eastern Saudi Arabian adult male population. (www.actabiomedica.it)